2015
DOI: 10.1017/s0007114515002093
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade inflammation, diet composition and health: current research evidence and its translation

Abstract: The importance of chronic low-grade inflammation in the pathology of numerous age-related chronic conditions is now clear. An unresolved inflammatory response is likely to be involved from the early stages of disease development. The present position paper is the most recent in a series produced by the International Life Sciences Institute's European Branch (ILSI Europe). It is co-authored by the speakers from a 2013 workshop led by the Obesity and Diabetes Task Force entitled ‘Low-grade inflammation, a high-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
574
1
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 692 publications
(595 citation statements)
references
References 152 publications
5
574
1
15
Order By: Relevance
“…Primary focus has been on the effect of individual dietary components on inflammation and metabolic health. Diet-derived antiinflammatory and anti-oxidative compounds in combination could potentially target multiple components of inflammation and metabolic stress in an additive or synergistic manner (106,107) . A study by Bakker et al showed that a combination of anti-inflammatory nutrients in overweight men increased adiponectin by 7 %, independent of weight loss, as well as influencing AT inflammation, oxidative stress and metabolism.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…Primary focus has been on the effect of individual dietary components on inflammation and metabolic health. Diet-derived antiinflammatory and anti-oxidative compounds in combination could potentially target multiple components of inflammation and metabolic stress in an additive or synergistic manner (106,107) . A study by Bakker et al showed that a combination of anti-inflammatory nutrients in overweight men increased adiponectin by 7 %, independent of weight loss, as well as influencing AT inflammation, oxidative stress and metabolism.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…They can also reduce the risk of the development of nutrition-related non-communicable diseases. 4 These health and disease states are mainly influenced by the individual fatty acid composition of the fats and oils consumed. The degree of saturation and the total amount and ratio of n-6 to n-3 fatty acids in the diet are of the essence.…”
Section: Perspectives On the Use Of Seed Oils In The South African Dietmentioning
confidence: 99%
“…[11][12][13] Omega-6 PUFAs are generally regarded as precursors of pro-inflammatory metabolites, which signal for the start of inflammation, and n-3 PUFAs as precursors for metabolites with anti-inflammatory properties, which on the other hand facilitate the termination of inflammation. 14,15 Both these functions are vital for human health, 4 and thus balancing the intake of n-6 and n-3 PUFAs is essential. 4,14 Furthermore, evidence that dietary SFAs also switch on proinflammatory mechanisms is accumulating.…”
Section: Perspectives On the Use Of Seed Oils In The South African Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the place of saturated dietary fats in the etiology of type 2 diabetes mellitus has been challenged in recent years, data from observational controlled experimental studies suggesting that replacing saturated and trans fatty acids with polyunsaturated fatty acids can lower the risk of type 2 diabetes can not be ignored [13,14]. A substantial amount of evidence, suggests that many foods especially dietary fats may affect inflammatory processes both acutely and chronically and low-grade inflammation is suspected to be involved in the cardiometabolic syndrome, increased risk of type 2 diabetes mellitus and cardiovascular disease associated with obesity [15].…”
Section: Introductionmentioning
confidence: 99%